Assessing genital human papillomavirus genoprevalence in young Australian women following the introduction of a national vaccination program. Issue 1 (1st January 2015) - Osborne, Sarah L.; Tabrizi, Sepehr N.; Brotherton, Julia M.L.; Cornall, Alyssa M.; Wark, John D.; Wrede, C. David; Jayasinghe, Yasmin; Gertig, Dorota M.; Pitts, Marian K.; Garland, Suzanne M.
Highlights: Prevalence of vaccine-targeted HPV genotypes was very low. HPV types 51, 59, 73, 84, and 89 were the most prevalent genotypes. Cohort vaccination rates were higher than reported in Victorian coverage data. Facebook proved effective in recruiting young women. Abstract: Objectives: Following the implementation of Australia's National HPV Vaccination Program in April 2007, this study evaluated the prevalence of vaccine-targeted human papillomavirus (HPV) genotypes (HPV 6, 11, 16, 18) amongst vaccine-eligible young women. Methods: Between September 2011 and August 2013, women from Victoria, Australia aged 18–25 were recruited through targeted advertising on the social networking website Facebook. Participants completed an online questionnaire, and sexually active women were asked to provide a self-collected vaginal swab for HPV deoxyribonucleic acid (DNA) detection and genotyping. Samples positive for HPV were genotyped using the Linear Array HPV genotyping test (Roche Diagnostics). Self-reported HPV vaccination details were verified with the National HPV Vaccination Program Register (NHVPR). Results: Of 431 vaginal swabs, 24.8% were positive for HPV DNA. Vaccine-targeted HPV genotypes were detected in only seven (1.6%) samples; all HPV 16 (of the six HPV 16 positive vaccinated women, all had received the vaccine after sexual debut). There were no cases of HPV 6, 11 or 18 identified. HPV types 51, 59, 73, 84, and 89 were the most prevalent genotypes. Vaccination rates were high, with 77.3% of participants having received all three doses of the vaccine, and there was an 89.8% concordance between self-reported and registry-reported HPV vaccination status. Strong associations were observed between vaccination status, age, language spoken at home and country of birth, as well as between HPV detection and the number of male sexual partners. Conclusion: Preliminary data from this study demonstrate a very low prevalence of vaccine-related HPV genotypes amongst vaccine-eligible women from Victoria, Australia. We were able to use Facebook to effectively reach and recruit young women to participate in the assessment of the impact of Australia's HPV vaccination program.